The Effect of Corporate Social Responsibility and Good Corporate Governance Disclosure on The Reputation of Banking Companies Listed on The Indonesia Stock Exchange (IDX) - M Sultan; Ni Made Dwi Ratnadi (International Journal of Economics, Commerce, and Management, 2025)
The purpose of the study is to provide empirical evidence regarding the influence of Corporate Social Responsibility and Good Corporate Governance Disclosure on Company Reputation. This research was conducted on banking companies listed on the Indonesia Stock Exchange (IDX) in 2020-2022. The number of samples taken was 108 observational samples, the nonprobability sampling method, especially the sampling technique, namely purposive sampling. Data collection is carried out by documentation. The analysis technique used is logistic regression analysis technique with the help of SPSS software. The results of this study show that Corporate Social Responsibility Disclosure has a positive effect on the company's reputation and Good Corporate Governance has a positive effect on the company's reputation.